Fortran, C and C++ code for econometrics and optimisation applications. - Orszag, J. Michael (Economic Journal, 1997)
The writer reviews some of the wide variety of computer software and related material available for use by economists. He discusses Fortran, C, and C++ code available freely in source form for econometrics and optimization applications. Given that there is so much freely available Fortran and C code for numerical applications relevant to economics, he concentrates on particular econometrics and nonlinear/linear programming software that he found useful. He states that free software is quite easy to download from the network and test, unlike commercial software, and therefore his goal is more to provide pointers to resources that might be mentioned elsewhere than to provide detailed reviews of individual packages. Among the packages he discusses are LOESS; GCV; NLMDL; the Standards Time Series and Regression Pack, or STARPAC; LANCELOT; NPSOL; and MINOS. In addition, he provides pointers on where to look for more information on these packages and pointers to other resources.